Informal caregiver burden of hospitalized patients during the COVID-19 pandemic (Research, Society and Development, 2022)
Introduction: The experience of hospitalization can generate several emotional manifestations for the caregiver, since they suffer from restrictions and give up their personal life while dedicating themselves to the care of others. Factors such as the level of dependence of the hospitalized patient can directly influence the burden of their caregiver, as well as other factors, including the fear of contamination by COVID-19 during the pandemic context experienced. Aim: To identify the factors associated with the burden of informal caregivers of hospitalized patients during COVID-19 pandemic. Method: Epidemiological, descriptive, cross-sectional study conducted with caregivers of hospitalized patients admitted to a university hospital. Sociodemographic data were collected and standardized assessments of the Katz Index, the Zarit Burden Interview Scale and the COVID-19 Fear Scale were applied. Data were analyzed with descriptive statistics and the chi-square test was used to establish statistical relationships between caregivers burden and other variables. Results: 33 informal caregivers were included. The caregiver burden was observed in 60.6% of caregivers and a significant association between “Caregiver burden” and the variables “Previous Katz Index”, “Exclusive caregiver” and “Average time working on weekdays”. Final considerations: The fact of being an exclusive caregiver and staying in the hospital for more days a week were associated with caregiver burden, in addition to the previous dependence on those assisted. Fear of COVID-19 was not associated with overload.